WAQF ASSET MANAGEMENT STRATEGY FOR IMPROVING PUBLIC HEALTH IN EAST JAVA PROVINCE - Indahsari, Sintia; Umar Ali, Rizki; Kurnia, Tuti; Alhifni, Anas (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2025)
This research aims to determine waqf asset management strategies for improving public health in East Java Province. The method used is qualitative with a descriptive approach and determining waqf management strategies using the SWOT analysis technique. The technique used in sampling is purposive sampling. Data collection techniques were carried out by distributing questionnaires and conducting interviews. This research indicates that waqf asset management in East Java Province is still widely used for religious and educational purposes. Meanwhile, the management of waqf assets by the Indonesian Waqf Board East Java is still doing little to improve public health. Hence, an appropriate strategy for managing waqf assets is establishing cooperation between the Indonesian Waqf Board and the Health Service to provide free ambulances and develop livestock waqf proceeds for programs for people experiencing poverty in prevention and control. disease, developing waqf land by building healthy houses, and developing waqf land by establishing nutritional recovery centers.